Nickel oxide composite electrode material and preparation method thereof
By optimizing the raw materials and preparation process of nickel oxide composite electrode materials, the problems of poor conductivity, insufficient cycle stability and high cost of traditional nickel oxide electrodes have been solved, realizing an electrode material with high conductivity, cycle stability and low cost, which is suitable for high-performance batteries.
Patent Information
- Application Number
- CN202510808626.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-10-24
AI Technical Summary
Traditional nickel oxide electrode materials suffer from poor conductivity, insufficient cycle stability, low rate performance, and high cost, which limits their application in high-performance batteries.
By using nickel oxide composite electrode materials and optimizing the raw material composition and preparation process, including the synergistic effect of silver nanowires and graphene, the heterostructure of lithium iron phosphate and nickel oxide, inert gas protected heat treatment, and optimized bonding system, a highly efficient conductive network and stable structure are formed, which improves the conductivity, cycle stability and reduces the cost of the electrode.
It significantly improves the conductivity and rate performance of the electrode, extends cycle life, and reduces material costs, enabling the electrode to perform excellently in high-power and long-life applications.
Smart Images

Figure CN120834173A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of battery materials, in particular to a nickel oxide composite electrode material and a preparation method thereof. BACKGROUND
[0002] With the continuous growth of global energy demand and the increasing awareness of environmental protection, the research and application of new energy materials have become an important direction in the field of science and technology. Among many new energy materials, lithium-ion batteries are highly concerned due to their high energy density, long cycle life and good rate performance.
[0003] However, traditional nickel oxide electrode materials have many defects in practical application. First, nickel oxide itself is an insulator with extremely poor conductivity. In the process of battery charging and discharging, the electrode material needs to have good conductivity to quickly conduct electrons, and the low conductivity of nickel oxide will increase the internal resistance of the battery, making the polarization phenomenon of the battery serious during charging and discharging, thereby reducing the charging and discharging efficiency of the battery and limiting its application in high-power demand scenarios.
[0004] Secondly, the cycle stability of nickel oxide electrode is insufficient. In the repeated charging and discharging process of the battery, the structure of the nickel oxide electrode material will change, such as particle agglomeration and collapse of the crystal structure. These structural changes will reduce the effective specific surface area of the electrode material, reduce the contact area between the electrolyte and the electrode material, and thus affect the charging and discharging performance of the battery, so that the capacity of the battery rapidly decays after multiple cycles, which cannot meet the requirement of high-performance batteries for long cycle life.
[0005] Furthermore, the rate performance of nickel oxide electrode is low. Rate performance refers to the performance of the battery under large current charging and discharging conditions. Due to the poor conductivity and insufficient structural stability of nickel oxide, the ion diffusion and electron conduction speed inside the electrode material cannot meet the requirements of fast charging and discharging under large current conditions, resulting in that the battery cannot realize fast charging and high-power discharging under large current conditions, which limits its application in devices requiring fast charging and discharging, such as the fast charging scenario of electric vehicles.
[0006] Finally, the cost of nickel oxide material is relatively high. The preparation process of nickel oxide is relatively complex, which requires high temperature and specific synthesis conditions, increasing the production cost. In addition, the problems of low conductivity and insufficient cycle stability of nickel oxide result in its low actual utilization rate in batteries, further increasing the unit cost of the battery, making the nickel oxide electrode face challenges in cost in large-scale commercial application.
[0007] These problems limit the application of nickel oxide electrode in high-performance batteries. Therefore, it is particularly important to develop a nickel oxide composite electrode material with excellent conductivity, high cycle stability, good rate performance and low cost. SUMMARY
[0008] (I) Technical problems to be solved
[0009] In view of the deficiencies in the prior art, the present application provides a nickel oxide composite electrode material and a preparation method thereof, which has the advantages of excellent conductivity, high cycle stability, good rate performance and low material cost, and solves the problems of poor conductivity, poor cycle stability, poor rate performance and high material cost of traditional nickel oxide electrodes.
[0010] (II) Technical solutions
[0011] To achieve the above-mentioned purpose, the present application provides the following technical solutions: a nickel oxide composite electrode material, the raw material components and their weight ratios of the electrode material are as follows: nickel oxide 25%-30%; graphene 10%-15%; silver nanowire 3%-5%; silver fiber 5%-8%; nitrogen-doped carbon nanotube 4%-6%; polyvinylidene fluoride 5%-8%; lithium iron phosphate 10%-15%; polyaniline 3%-6%; carbon black 3%-5%; polypyrrole 2%-4%; sodium carboxymethyl cellulose 1%-3%; N-methyl pyrrolidone 5%-10%; hydroxypropyl methyl cellulose 2%-4%; lithium cobaltate 5%-10%.
[0012] Preferably, the raw material components and their weight ratios of the electrode material are as follows: nickel oxide 28%; graphene 13%; silver nanowire 4%; silver fiber 6%; nitrogen-doped carbon nanotube 5%; polyvinylidene fluoride 6%; lithium iron phosphate 12%; polyaniline 4%; carbon black 4%; polypyrrole 3%; sodium carboxymethyl cellulose 2%; N-methyl pyrrolidone 8%; hydroxypropyl methyl cellulose 3%; lithium cobaltate 7%.
[0013] Preferably, the nitrogen-doped carbon nanotube is prepared by a chemical vapor deposition method, and the chemical reaction formula is as follows:
[0014] C3H6N+NiO→N-CNT+Ni
[0015] During the reaction, acetonitrile reacts with the nickel catalyst to generate nitrogen-doped carbon nanotubes.
[0016] A preparation method of a nickel oxide composite electrode material, according to the raw material components and their weight ratios of the above-mentioned nickel oxide composite electrode material, comprises the following preparation steps:
[0017] Step one, formula preparation: prepare the formula weight ratio of nickel oxide, graphene, silver nanowire, silver fiber, nitrogen-doped carbon nanotube, polyvinylidene fluoride, lithium iron phosphate, polyaniline, carbon black, polypyrrole, sodium carboxymethyl cellulose, N-methyl pyrrolidone, hydroxypropyl methyl cellulose and lithium cobaltate;
[0018] Step two, raw material component pretreatment: pretreatment of nickel oxide, graphene, silver nanowire and nitrogen-doped carbon nanotube;
[0019] Step three, raw material component mixing: under dry environment, mix nickel oxide, lithium iron phosphate, lithium cobaltate, carbon black, graphene, silver nanowire, silver fiber and nitrogen-doped carbon nanotube to obtain a solid mixture, dissolve polyvinylidene fluoride, hydroxypropyl methyl cellulose, N-methyl pyrrolidone, sodium carboxymethyl cellulose, polyaniline and polypyrrole in water bath environment to obtain a liquid component, add the liquid component dropwise into the solid mixture to form a precursor of electrode material;
[0020] Step four, coating and forming: combine the precursor of electrode material with the conductive substrate, dry and press to form;
[0021] Step five, heat treatment: heat treat the formed electrode under argon.
[0022] Preferably, in the step two, the raw material component pretreatment: dry the nickel oxide under the environment of vacuum degree ≤5Pa and temperature 115-120℃ for 3-4h.
[0023] Preferably, in the step two, the raw material component pretreatment: ultrasonically disperse the graphene and silver nanowire in 0.1±0.005mol / L ethanol solution for 25-30min respectively; ultrasonically disperse the prepared nitrogen-doped carbon nanotube in deionized water for 15-20min.
[0024] Preferably, in the step three, the raw material component mixing step is:
[0025] S3.1, add nickel oxide, lithium iron phosphate, lithium cobaltate and carbon black into a three-dimensional mixer in sequence and preliminarily mix;
[0026] S3.2, add graphene, silver nanowire, silver fiber and nitrogen-doped carbon nanotube into the three-dimensional mixer in sequence, and then add zirconium oxide balls with ball-to-material ratio of 6:1, and ball mill mix at a speed of 100-200rpm for 2-3h;
[0027] S3.3, dissolve polyvinylidene fluoride and hydroxypropyl methyl cellulose in N-methyl pyrrolidone under water bath environment of 55-60℃, and stir for 1.5-2h;
[0028] S3.4, adding sodium carboxymethyl cellulose, polyaniline and polypyrrole to the solution of S3.3, and continuing to stir until the viscosity of the mixed liquid reaches 4200±200 mPa·s.
[0029] S3.5, dropwise adding the liquid component treated in S3.4 to the solid mixture of S3.2 which has been mixed sufficiently;
[0030] S3.6, stirring the mixture of S3.5 in a stirrer at a rotation speed of 1000-1200 rpm and a vacuum degree of-0.05 MPa to-0.08 MPa for 0.5-1 h.
[0031] Preferably, the coating forming conditions are: the coating thickness is 0.5-1.0 mm, the drying temperature is 70-75℃, and the drying time is 12-14 h; the heat treatment conditions are: the heat treatment temperature is 250-300℃, and the holding time is 1.5-2 h.
[0032] Preferably, the silver nanowires and graphene form a two-dimensional+one-dimensional synergistic conduction.
[0033] Preferably, the lithium iron phosphate and nickel oxide NiO form a heterostructure by a hydrothermal method, and the chemical reaction formula is:
[0034] Ni 2+ + LiFePO4→ NiO + LiFePO4
[0035] During the reaction, the lithium iron phosphate acts as a buffer layer.
[0036] Compared with the prior art, the present application provides a nickel oxide composite electrode material and a preparation method thereof, which has the following beneficial effects:
[0037] 1、The present application optimizes the type and proportion of the conductive agent in the raw material composition to improve the conductivity and rate performance of the electrode, wherein the synergistic effect of silver nanowires and graphene is used to construct an efficient conductive network to improve the conductivity of the electrode, and this efficient conductive network not only improves the specific capacity of the electrode at low rates, but also improves the performance at high rates, effectively solving the problems of poor conductivity and insufficient rate performance of traditional nickel oxide electrodes, and making the electrode have better performance in high-rate applications.
[0038] 2、The application forms a heterostructure of lithium iron phosphate and nickel oxide, improves the cycle stability of the electrode and reduces the volume expansion rate, wherein the lithium iron phosphate and the nickel oxide form a heterostructure through a hydrothermal method, the structure can effectively alleviate the volume change of the nickel oxide in the charging and discharging process, thereby improving the structural stability and cycle life of the electrode, effectively solving the problems of poor cycle stability and large volume expansion of the traditional nickel oxide electrode, and enabling the electrode to maintain stable performance in the long-term charging and discharging process.
[0039] 3、The application adopts inert gas protection heat treatment and optimizes the bonding system, enhances the structural stability of the electrode and reduces the material cost, adopts heat treatment under argon protection to avoid oxidation of the silver nanowire, improves the conductivity of the composite electrode, enhances the structural stability of the electrode, and optimizes the bonding system to increase the proportion of polyvinylidene fluoride and hydroxypropyl methyl cellulose, further improves the mechanical strength and stability of the electrode. BRIEF DESCRIPTION OF DRAWINGS
[0040] Figure 1 The flow chart for preparing the application is shown in the figure. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the application will be described clearly and completely below with reference to the accompanying drawings in the embodiments of the application. Obviously, the described embodiments are only part of the embodiments of the application, rather than all the embodiments of the application. Based on the embodiments in the application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the application.
[0042] Please refer to Figure 1The raw material components and their weight ratios of the electrode material are as follows: 25-30% of nickel oxide (NiO) as the main body of the electrode material, providing basic electrochemical performance and energy storage capacity; 10-15% of graphene, which can enhance the conductivity of the electrode, build an efficient conductive network, and promote the rapid transmission of electrons; 3-5% of silver nanowires, which can further improve the conductivity of the electrode, especially providing a faster electron channel during high-rate charging and discharging; 5-8% of silver fibers, which increase the conductivity and mechanical strength of the electrode and help form a stable electrode structure; 4-6% of nitrogen-doped carbon nanotubes, which improve the conductivity and capacitance characteristics of the electrode and increase the electrochemical activity; 5-8% of polyvinylidene fluoride (PVDF) as a binder to bond the electrode material particles together and maintain the stability of the electrode structure; 10-15% of lithium iron phosphate (LiFePO4), which cooperates with nickel oxide to improve the capacity and cycle stability of the electrode; 3-6% of polyaniline (PANI), which increases the conductivity and electrochemical activity of the electrode and assists in storing electric charge; 3-5% of carbon black, which enhances the conductivity of the electrode and forms more conductive channels in the material; 2-4% of polypyrrole (PPy), which improves the conductivity and electrochemical performance of the electrode and cooperates with other materials; 1-3% of sodium carboxymethyl cellulose (CMC) as a thickening agent and dispersant to adjust the viscosity and rheological properties of the electrode material and make the material uniformly dispersed; 5-10% of N-methyl pyrrolidone (NMP) as a dispersant to ensure that various materials are uniformly dispersed during the preparation process and avoid agglomeration; 2-4% of hydroxypropyl methyl cellulose (HPMC) to further adjust the rheological properties of the electrode material for easy coating and molding; and 5-10% of lithium cobalt oxide (LiCoO2) as an active additive to improve the electrochemical performance and capacity of the electrode.
[0043] The advantages of the present application are that by optimizing the types and proportions of conductive agents in the raw material components, the conductivity and rate performance of the electrode are improved, and by the synergistic effect of silver nanowires and graphene, an efficient conductive network is built to improve the conductivity of the electrode.
[0044] Specifically, the nitrogen-doped carbon nanotubes are prepared by a chemical vapor deposition (CVD) method, and the chemical reaction formula is as follows:
[0045] C3H6N + NiO → N-CNT + Ni
[0046] During the reaction, acetonitrile reacts with the nickel catalyst to generate nitrogen-doped carbon nanotubes.
[0047] Specifically, a preparation method of a nickel oxide composite electrode material is prepared according to the raw material components and their weight ratios of the nickel oxide composite electrode material described above, and includes the following preparation steps:
[0048] Step one, formula preparation: prepare the formula weight ratio of nickel oxide, graphene, silver nanowire, silver fiber, nitrogen-doped carbon nanotube, polyvinylidene fluoride, lithium iron phosphate, polyaniline, carbon black, polypyrrole, sodium carboxymethyl cellulose, N-methyl pyrrolidone, hydroxypropyl methyl cellulose and lithium cobaltate;
[0049] Step two, raw material component pretreatment: pretreat the nickel oxide, graphene, silver nanowire and nitrogen-doped carbon nanotube;
[0050] Step three, raw material component mixing: in a dry environment, mix the nickel oxide, lithium iron phosphate, lithium cobaltate, carbon black, graphene, silver nanowire, silver fiber and nitrogen-doped carbon nanotube to obtain a solid mixture, mix the liquid components obtained by mixing polyvinylidene fluoride, hydroxypropyl methyl cellulose, N-methyl pyrrolidone, sodium carboxymethyl cellulose, polyaniline and polypyrrole, and add the liquid components drop by drop into the solid mixture to form a precursor of the electrode material;
[0051] Step four, coating and molding: combine the precursor of the electrode material with a conductive substrate (such as copper foil or aluminum foil, etc.), dry and then press to form;
[0052] Step five, heat treatment: heat treat the formed electrode under argon to enhance the structural stability of the material.
[0053] Specifically, in step two, the raw material components are pretreated: dry the nickel oxide at a vacuum degree of ≤5 Pa and a temperature of 115-120℃ for 3-4h to remove adsorbed water.
[0054] Specifically, in step two, the raw material components are pretreated: ultrasonically disperse the graphene and silver nanowire in 0.1±0.005 mol / L ethanol solution for 25-30 min to improve their dispersibility; ultrasonically disperse the prepared nitrogen-doped carbon nanotube in deionized water for 15-20 min to ensure uniform dispersion.
[0055] Specifically, in step three, the raw material component mixing step is:
[0056] S3.1, add the nickel oxide, lithium iron phosphate, lithium cobaltate and carbon black into a three-dimensional mixer in turn, and preliminarily mix to ensure uniform distribution of the main active substances (nickel oxide, lithium iron phosphate, lithium cobaltate) and the conductive additive (carbon black);
[0057] S3.2, add graphene, silver nanowires, silver fibers and nitrogen-doped carbon nanotubes into the three-dimensional mixer in order, then add zirconia balls with a ball-to-material ratio of 6:1, and ball mill for 2-3 hours at a speed of 100-200 rpm to fully mix the solid raw materials, and the two-dimensional + one-dimensional synergistic conductive network of graphene and silver nanowires improves the conductivity of the electrode, and the silver fibers further enhance the mechanical strength and conductivity, especially during high-rate charging and discharging;
[0058] S3.3, dissolve polyvinylidene fluoride and hydroxypropyl methylcellulose in N-methyl pyrrolidone under water bath at 55-60℃, and stir for 1.5-2 hours, and water bath heating and stirring can ensure the complete dissolution of polyvinylidene fluoride and hydroxypropyl methylcellulose to form a uniform liquid component;
[0059] S3.4, add sodium carboxymethyl cellulose, polyaniline and polypyrrole to the solution of S3.3, and continue to stir until the viscosity of the mixed liquid reaches 4200±200 mPa·s, and the polyaniline and polypyrrole as conductive polymers can further improve the conductivity and electrochemical activity of the electrode.
[0060] S3.5, drop the liquid component obtained by S3.4 into the solid mixture of S3.2 which has been fully mixed, and through the dropwise addition of the liquid component, the uniform combination of the liquid and solid components is ensured, and local over-wetting or over-drying is avoided, and the overall uniformity of the electrode is improved;
[0061] S3.6, stir the mixture of S3.5 in a stirrer at a speed of 1000-1200 rpm and a vacuum degree of -0.05 MPa to -0.08 MPa for 0.5-1 hour, and the above steps can ensure that all raw material components are uniformly mixed, and the entire raw material component mixing process is completed, wherein high-speed stirring and vacuum environment can ensure the uniform mixing of all components, eliminate bubbles and unevenness, and thus improve the performance consistency of the composite electrode.
[0062] The advantages are: by adopting inert gas protection heat treatment and optimizing the bonding system, the beneficial effects of enhancing the structural stability of the electrode and reducing the cost of the material are achieved, by adopting heat treatment under argon protection, the oxidation of silver nanowires is avoided, the conductivity of the composite electrode is improved, and the structural stability of the electrode is enhanced, and at the same time, by optimizing the bonding system, the proportion of polyvinylidene fluoride and hydroxypropyl methylcellulose is increased, and the mechanical strength and stability of the electrode are further improved.
[0063] Specifically, the coating forming conditions are: coating thickness is 0.5-1.0 mm, drying temperature is 70-75℃, and drying time is 12-14 hours; the heat treatment conditions are: heat treatment temperature is 250-300℃, and holding time is 1.5-2 hours.
[0064] Specifically, the silver nanowires and the graphene form two-dimensional + one-dimensional synergistic conduction, the high conductivity and the aspect ratio of the silver nanowires are combined with the two-dimensional structure of the graphene, the conductivity and the electron transmission efficiency of the electrode are effectively improved, the internal resistance of the electrode can be effectively reduced, and the rate performance and the cycle stability of the electrode are improved.
[0065] Specifically, the lithium iron phosphate and the nickel oxide NiO form a heterostructure through a hydrothermal method, the structure can improve the capacity and the cycle stability of the electrode, and a chemical reaction formula is as follows:
[0066] Ni 2+ +LiFePO4→NiO+LiFePO4
[0067] During the reaction, the lithium iron phosphate acts as a buffer layer, and can effectively alleviate the volume change of the nickel oxide in the charging and discharging process.
[0068] The heterostructure of the lithium iron phosphate and the nickel oxide is formed, the cycle stability of the electrode is improved, and the volume expansion rate is reduced, the lithium iron phosphate and the nickel oxide form a heterostructure through a hydrothermal method, the structure can effectively alleviate the volume change of the nickel oxide in the charging and discharging process, the structural stability and the cycle life of the electrode are improved, the problems of the poor cycle stability and the large volume expansion of the traditional nickel oxide electrode are solved, and the electrode can maintain stable performance in the long-term charging and discharging process.
[0069] Example 1
[0070] The raw material components and the weight ratio of the electrode material are as follows: 28% of nickel oxide, 13% of graphene, 4% of silver nanowires, 6% of silver fiber, 5% of nitrogen-doped carbon nanotubes, 6% of polyvinylidene fluoride, 12% of lithium iron phosphate, 4% of polyaniline, 4% of carbon black, 3% of polypyrrole, 2% of sodium carboxymethyl cellulose, 8% of N-methylpyrrolidone, 3% of hydroxypropyl methyl cellulose, and 7% of lithium cobaltate.
[0071] Example 2
[0072] The fine-tuning conductive agent ratio is as follows: 12% of graphene, 5% of silver nanowires, and 6% of nitrogen-doped carbon nanotubes (other raw material components are the same as those in Example 1).
[0073] Example 3
[0074] The optimized bonding system is as follows: 7% of polyvinylidene fluoride and 4% of hydroxypropyl methyl cellulose (other raw material components are the same as those in Example 1).
[0075] Comparative Examples 1-3 (adjustment of raw material components)
[0076] Comparative Example 1
[0077] The silver nanowires are reduced to 1%, and the silver fiber is deleted.
[0078] Comparative Example 2
[0079] Replace graphene with carbon black (addition amount 15%).
[0080] Comparative Example 3
[0081] Remove LiFePO4; increase NiO to 35%.
[0082] Comparative Example 4 (process adjustment, formula raw material composition same as Example 1)
[0083] T1, pretreatment process: cancel NiO vacuum drying, change to 80°C normal pressure drying;
[0084] T2, mixing order: first mix liquid components, then add solid materials;
[0085] T3, heat treatment condition: 300°C treatment for 2h under air atmosphere (non-inert gas).
[0086] The example and comparative example are made into finished product composite electrode material, and its performance test, comparative data Table 1 is as follows:
[0087] Table 1
[0088]
[0089]
[0090] From Table 1, the following information is obtained:
[0091] Comparative Example 1 and Comparative Examples 1-2
[0092] Silver nanowires (4%) + graphene (13%) synergistically increase conductivity by 5.1 times (920 vs. 180 S / cm), and carbon black cannot build an effective conductive network (the conductivity of Comparative Example 2 is only 80 S / cm);
[0093] Comparative Example 1 and Comparative Example 3
[0094] LiFePO4-coated NiO increases cycle retention rate by 121% (93% vs. 42%), and reduces volume expansion by 76.7%;
[0095] Comparative Example 1 and Comparative Example 4
[0096] Inert gas heat treatment increases conductivity by 268% (920 vs. 250 S / cm), and air heat treatment leads to silver oxidation failure.
[0097] Summary: The specific capacity (+112%), cycle life (+63%), rate capability (+267%) of the application are overall superior to traditional NiO electrodes, wherein the silver nanowire dosage in the application is only 4% (traditional silver powder electrode needs 10%), which reduces the material cost by 36%, through the raw material component ratio-process synergistic design, the problems of poor conductivity, poor cycle stability, poor rate performance and high material cost of traditional nickel oxide electrode are solved, which provides a new idea and method for the development of high-performance supercapacitor and battery electrode materials.
[0098] While embodiments of the application have been shown and described, it is to be understood that the embodiments described are merely exemplary of the principles and application of the present application. Numerous modifications and adaptions can be made without departing from the spirit and scope of the present application, which is defined by the following claims and their equivalents.
Claims
1. A nickel oxide composite electrode material, characterized in that, The raw material components and their weight ratios of the electrode material are as follows: 25%-30% of nickel oxide, 10%-15% of graphene, 3%-5% of silver nanowire, 5%-8% of silver fiber, 4%-6% of nitrogen-doped carbon nanotube, 5%-8% of polyvinylidene fluoride, 10%-15% of lithium iron phosphate, 3%-6% of polyaniline, 3%-5% of carbon black, 2%-4% of polypyrrole, 1%-3% of sodium carboxymethyl cellulose, 5%-10% of N-methyl pyrrolidone, 2%-4% of hydroxypropyl methyl cellulose, and 5%-10% of lithium cobaltate.
2. The nickel oxide composite electrode material according to claim 1, characterized in that: The raw material components and their weight ratios of the electrode material are as follows: 25%-30% of nickel oxide, 10%-15% of graphene, 3%-5% of silver nanowire, 5%-8% of silver fiber, 4%-6% of nitrogen-doped carbon nanotube, 5%-8% of polyvinylidene fluoride, 10%-15% of lithium iron phosphate, 3%-6% of polyaniline, 3%-5% of carbon black, 2%-4% of polypyrrole, 1%-3% of sodium carboxymethyl cellulose, 5%-10% of N-methyl pyrrolidone, 2%-4% of hydroxypropyl methyl cellulose, and 5%-10% of lithium cobaltate. The raw material components and their weight ratios of the electrode material are as follows: 25%-30% of nickel oxide, 10%-15% of graphene, 3%-5% of silver nanowire, 5%-8% of silver fiber, 4%-6% of nitrogen-doped carbon nanotube, 5%-8% of polyvinylidene fluoride, 10%-15% of lithium iron phosphate, 3%-6% of polyaniline, 3%-5% of carbon black, 2%-4% of polypyrrole, 1%-3% of sodium carboxymethyl cellulose, 5%-10% of N-methyl pyrrolidone, 2%-4% of hydroxypropyl methyl cellulose, and 5%-10% of lithium cobaltate.
3. The nickel oxide composite electrode material of claim 1, wherein: The nitrogen-doped carbon nanotube is prepared by a chemical vapor deposition method, and the chemical reaction formula is as follows: C3H6N+NiO→N-CNT+Ni During the reaction, acetonitrile reacts with the nickel catalyst to generate nitrogen-doped carbon nanotubes.
4. A method for preparing a nickel oxide composite electrode material, characterized by, The raw material components and their weight ratios of the electrode material are prepared according to claim 1, and the preparation includes the following steps: Step one, formula preparation: prepare the raw material components of the electrode material in the weight ratios of nickel oxide, graphene, silver nanowire, silver fiber, nitrogen-doped carbon nanotube, polyvinylidene fluoride, lithium iron phosphate, polyaniline, carbon black, polypyrrole, sodium carboxymethyl cellulose, N-methyl pyrrolidone, hydroxypropyl methyl cellulose, and lithium cobaltate; Step two, raw material component pretreatment: pretreat the nickel oxide, graphene, silver nanowire, and nitrogen-doped carbon nanotube; Step three, raw material component mixing: in a dry environment, mix the nickel oxide, lithium iron phosphate, lithium cobaltate, carbon black, graphene, silver nanowire, silver fiber, and nitrogen-doped carbon nanotube to obtain a solid mixture, mix the polyvinylidene fluoride, hydroxypropyl methyl cellulose, N-methyl pyrrolidone, sodium carboxymethyl cellulose, polyaniline, and polypyrrole in a water bath environment to obtain a liquid component, and add the liquid component drop by drop into the solid mixture to form a precursor of the electrode material; Step four, coating and molding: combine the precursor of the electrode material with a conductive substrate, dry, and then press to form; Step five, heat treatment: heat treat the formed electrode under argon.
5. The method for preparing a nickel oxide composite electrode material according to claim 4, characterized in that: In the raw material component pretreatment in step two, the nickel oxide is dried at a vacuum degree of ≤5 Pa and a temperature of 115-120℃ for 3-4 h.
6. The method for preparing a nickel oxide composite electrode material according to claim 4, characterized in that: In the raw material component pretreatment in step two, the graphene and silver nanowire are respectively placed in a 0.1±0.005 mol / L ethanol solution for ultrasonic dispersion for 25-30 min, and the prepared nitrogen-doped carbon nanotube is ultrasonically dispersed in deionized water for 15-20 min.
7. The method according to claim 4, wherein the method is characterized by: In the raw material component mixing step in step three, the following steps are included: S3.1, sequentially add the nickel oxide, lithium iron phosphate, lithium cobaltate, and carbon black into a three-dimensional mixer for preliminary mixing; S3.2, sequentially adding graphene, silver nanowires, silver fibers and nitrogen-doped carbon nanotubes into a three-dimensional mixer, then adding zirconia balls with a ball-to-material ratio of 6:1, and ball-milling at a speed of 100-200 rpm for 2-3 h; S3.3, dissolving polyvinylidene fluoride and hydroxypropyl methyl cellulose in N-methyl pyrrolidone under a water bath at 55-60℃, and stirring for 1.5-2 h; S3.4, adding sodium carboxymethyl cellulose, polyaniline and polypyrrole into the solution of S3.3, and continuing to stir until the viscosity of the mixed liquid reaches 4200±200 mPa·s. S3.5, adding the liquid component obtained by S3.4 into the solid mixture of S3.2 drop by drop; S3.6, stirring the mixture of S3.5 in a stirrer at a speed of 1000-1200 rpm and a vacuum degree of-0.05 MPa to-0.08 MPa for 0.5-1 h. 8.The method for preparing a nickel oxide composite electrode material according to claim 4, characterized in that: The coating forming conditions are: the coating thickness is 0.5-1.0 mm, the drying temperature is 70-75℃, and the drying time is 12-14 h; the heat treatment conditions are: the heat treatment temperature is 250-300℃, and the holding time is 1.5-2 h.
9. The method according to claim 4, wherein the method is characterized by: The silver nanowires and graphene form two-dimensional+one-dimensional synergistic conduction.
10. The method for preparing a nickel oxide composite electrode material according to claim 4, characterized in that: The lithium iron phosphate forms a heterostructure with nickel oxide NiO by a hydrothermal method, and the chemical reaction formula is: Ni 2+ + LiFeP04→ NiO + LiFeP04 During the reaction, the lithium iron phosphate acts as a buffer layer.